GOOGLE TRENDS VERİLERİYLE COĞRAFİ İŞARETLİ GASTRONOMİK ÜRÜNLERİN ANALİZİ - Güleç, Enes; Şi̇mşek, Aykut; Solmaz, Rıdvan (Karabük Üniversitesi, 2022)
Google is one of the most used search engines in the world and is one of Google's most popular products. Google Trends, a sub-service of Google, analyzes search trends through Google. In this study, Adana, Antalya, Burdur, Hatay, Isparta, Kahramanmaras, Mersin and Osmaniye provinces in the Mediterranean region were included. First geographical indication registration of gastronomic products between 16/01/2015 - 16/01/2020 with Google search engine in Turkey in general "interest shown over time" and "the lower region of interest" is intended to examine the area. The terms “Adana Kebab, Antalya Piyazı, Burdur Walnut Butter, Künefe, Banak, Maras Tarhanası, Cezerye and Osmaniye Peanuts” were analyzed from 16 January 2015 to 16 January 2020 with Google Trends. It is seen that the products that receive geographical signs are in the first place in the provinces where they receive geographical signs. However, unlike the other selected geographical sign registered gastronomic products, it is noteworthy that künefe is popular in a city different from the city where it is geographically marked in the first place in the list of interests according to the sub-region. Osmaniye Groundnut is not a very popular search in Google search engine.

Google dünyada en çok kullanılan arama motorlarından biridir ve Google şirketinin en popüler ürünlerindendir. Google’ın bir alt servisi olan Google Trends, Google üzerinden yapılan arama eğilimlerini analiz etmektedir. Bu çalışmada, Akdeniz bölgesindeki Adana, Antalya, Burdur, Hatay, Isparta, Kahramanmaraş, Mersin ve Osmaniye illerinde ilk coğrafi işaret tescili alan gastronomik ürünlerin 16/01/2015 – 16/01/2020 tarihleri arasında Türkiye geneli Google arama motorunda “zaman içinde gösterilen ilgi” ve “alt bölgeye göre ilgi” alanını incelemeyi amaçlanmaktadır. “Adana Kebabı, Antalya Piyazı, Burdur Ceviz Ezmesi, Antakya Künefesi, Uluborlu Banağı, Maraş Tarhanası, Mersin Cezeryesi ve Osmaniye Yer Fıstığı” terimleri Google Trends ile 16 Ocak 2015'den 16 Ocak 2020'ye kadar analiz edilmiştir. Genellikle coğrafi işaret alan ürünler coğrafi işaret aldıkları illerde ilk sırada yer aldığı görülmüştür. Fakat seçilmiş diğer coğrafi işaret tescilli gastronomik ürünlerden farklı olarak künefenin alt bölgeye göre ilgi alanları sıralamasında ilk sırada coğrafi işaretli olduğu şehirden farklı bir şehirde popülerlik göstermesi dikkat çekmektedir. Osmaniye Yer Fıstığının Google arama motorunda çok fazla popüler bir arama olmadığı görülmüştür.
Keywords: Turizm (Diğer); Tourism (Other); Coğrafi İşaret; Google Trends; Gastronomik Ürün; Geographic Sign; Google Trends; Gastronomic Product; 2. Zero hunger